2022
DOI: 10.1186/s12888-022-04271-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination coverage among patients with psychiatric disorders in China during the pandemic: a cross-sectional study

Abstract: Background: To investigate the Coronavirus Disease 2019 (COVID-19) vaccination coverage and the influential factors of vaccination among patients with mental disorders, we conducted a cross-sectional study in China. Method: The anonymous questionnaires including demographic data, vaccination status, intention to be vaccinated and its reasons were collected in the Second Xiangya Hospital, one of the biggest four psychiatric centers in China. Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Even though low education levels were found to be associated with the prediction of a negative vaccination decision in this study, as in a recent Chinese study on vaccination coverage in psychiatric patients [ 64 ], the current study did not assess the psychological status of the patients. In addition, the Health Belief Model is not the only model that has proven useful in investigating the determinants of health-related behaviors, such as vaccination.…”
Section: Discussionmentioning
confidence: 61%
“…Even though low education levels were found to be associated with the prediction of a negative vaccination decision in this study, as in a recent Chinese study on vaccination coverage in psychiatric patients [ 64 ], the current study did not assess the psychological status of the patients. In addition, the Health Belief Model is not the only model that has proven useful in investigating the determinants of health-related behaviors, such as vaccination.…”
Section: Discussionmentioning
confidence: 61%
“…Twenty-one of the 33 reviewed studies identified patients with mental health conditions through clinical diagnoses obtained from medical records (Bai et al, 2021; Cai et al, 2022; Curtis, Inglesby, MacKenna, et al, 2022; Curtis, Inglesby, Morton, et al, 2022; Eyllon et al, 2022; Gibbon et al, 2021; Hassan et al, 2022; Jefsen et al, 2021; Mazereel et al, 2021; Moeller et al, 2021; Nilsson et al, 2022; Nishimi, Neylan, et al, 2022; Qin et al, 2022; Raffard et al, 2022; Ren et al, 2021; Shkalim Zemer et al, 2022; Sullivan et al, 2022; Tsai et al, 2022; Tzur Bitan et al, 2022; Uvais, 2022; L. Wang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen of the 33 reviewed studies reported on the association between mental health conditions and the uptake of the COVID-19 vaccine or booster vaccine (Table 2, Balut et al, 2021; Curtis, Inglesby, MacKenna, et al, 2022; Curtis, Inglesby, Morton, et al, 2022; Gibbon et al, 2021; Hassan et al, 2022; Huang et al, 2021; Mazereel et al, 2021; Moeller et al, 2021; Murphy et al, 2022; Nguyen et al, 2022; Nilsson et al, 2022; Qin et al, 2022; Raffard et al, 2022; Sekizawa et al, 2022; Shkalim Zemer et al, 2022; Tzur Bitan et al, 2022; Uvais, 2022). Sizes of the studies ranged from N=62 to 57.9 million.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations